2017
DOI: 10.1007/s12576-017-0526-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a simulated gravity load for atmospheric reentry, 10 g for 2 min, on conscious mice

Abstract: The Japan Aerospace Exploration Agency recently performed a mouse experiment in the International Space Station in which mice were raised for 35 days, retrieved using the Dragon spacecraft, and then harvested for analysis 2 days after splashdown. However, the impact of the retrieval procedure, which exposed mice to 5-10 g for 2 min during atmospheric reentry and splashdown, was unknown. Therefore, the purpose of this study was to examine the impact of a 10 g load for 2 min (using a gondola-type centrifuge with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Prior to the space experiment, we conducted various ground-based biocompatibility tests of the new hardware, as well as the Coriolis Effect, during short radius-centrifugation onboard and steady state acceleration during the launch and return phases 15 17 . The success of these ground-based biocompatibility tests convinced us to conduct space experiments with our new hardware.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the space experiment, we conducted various ground-based biocompatibility tests of the new hardware, as well as the Coriolis Effect, during short radius-centrifugation onboard and steady state acceleration during the launch and return phases 15 17 . The success of these ground-based biocompatibility tests convinced us to conduct space experiments with our new hardware.…”
Section: Introductionmentioning
confidence: 99%
“…Hypergravity exposure at 2 g increases the corticosterone concentration when it is measured during the first hour of exposure [63]. The increase in the hypergravity level can transiently increase the plasma corticosterone level [64]. Nevertheless, as our data showed, after 24 h of weak exposure at 2 g, the corticosterone levels were not altered in the first hour following the stop of the centrifuge [65].…”
Section: Discussionmentioning
confidence: 50%
“…Furthermore, numerous studies have reported that activation of vestibular-autonomic related brain areas was critical for the production of autonomic MS manifestations (Yates et al, 1999 ; Pompeiano et al, 2004 ; Balaban et al, 2014 ; Nalivaiko et al, 2014 ). Provocative motion stimulation could increase the expression of Fos protein (a marker of neuronal activity) in vestibulo-autonomic nuclei such as the caudal vestibular nucleus (CVN) including caudal medial and spinal vestibular nucleus, the nucleus of solitary tract (NTS), the parabrachial nucleus (PBN), the central nucleus of amygdala (CeA), and in stress-related areas such as the locus coeruleus (LC) and the paraventricular nucleus of hypothalamus (PVN) (Nakagawa et al, 2003 ; Cai et al, 2010 ; Balaban et al, 2014 ; Morita et al, 2017 ). These structures constitute neural networks that were believed to contribute to MS induced by vestibular stimulation (Balaban et al, 2014 ; Zhou et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Conditioned gaping response that can be elicited during exposure to a context previously paired with nauseant agents or provocative motion can be alleviated by corresponding anti-emetic and anti-MS drugs, making it plausible to serve as a rat model of conditioned nausea (Limebeer et al, 2008;Parker, 2014;Zhou et al, 2017;Qi et al, 2019;Rock et al, 2022). In addition, defecation response and decreased spontaneous locomotion activity were also observed in rats and mice exposed to whole-body rotation (Ossenkopp and Frisken, 1982;Ossenkopp et al, 1994;Yu et al, 2007;Limebeer et al, 2008;Morita et al, 2017;Wang et al, 2017;Deshetty et al, 2021). Balance disorder characterized by the decline in the time taken traversing balance beam was also elicited by passive motion stimulation in both rats and mice (Tung et al, 2014;Zhou et al, 2017;Manno et al, 2020;Zhong et al, 2022).…”
Section: Introductionmentioning
confidence: 99%